2003
DOI: 10.1016/s0304-3959(03)00091-5
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal pain in the obese: a comparison with a general population and long-term changes after conventional and surgical obesity treatment

Abstract: Obesity is associated with musculoskeletal pain and osteoarthritis. This study compares the prevalence of work-restricting musculoskeletal pain in an obese and a general population and investigates changes in the incidence of and recovery from musculoskeletal pain after bariatric surgery or conventional obesity treatment. A random sample of 1135 subjects from a general population was compared with 6328 obese subjects in the Swedish obese subjects (SOS) study. For the obese subjects, information about musculosk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
176
0
12

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(198 citation statements)
references
References 35 publications
10
176
0
12
Order By: Relevance
“…Schouten et al reported that disabilities could partly be due to cartilage loss, which is known to be strongly associated with knee OA and overweight (36) . Peltonen et al (37) concluded that obese subjects have more problems with work-restricting musculoskeletal pain than non-obese subjects. In a review Zamboni et al (38) found that body weight and BMI play a significant role in non-fatal physical disability in the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…Schouten et al reported that disabilities could partly be due to cartilage loss, which is known to be strongly associated with knee OA and overweight (36) . Peltonen et al (37) concluded that obese subjects have more problems with work-restricting musculoskeletal pain than non-obese subjects. In a review Zamboni et al (38) found that body weight and BMI play a significant role in non-fatal physical disability in the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…The percent of patients with lumbosacral spine complaints decreased from 62 to 11%, hip pain from 11 to 2%, knee complaints from 57 to 14%, ankle problems from 34 to 2% and foot pain from 21 to 1%. 17 Peltonen et al 1 looked at work-restricting MSK symptoms in the general population and 2010 surgically treated obese subjects, aged 37-60 years, and 2037 age-and gender-matched obese subjects not undergoing surgery. Obese subjects had more work-restricting neck, low back, hip, knee and ankle pain and the prevalence increased with BMI.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Physician bias towards obese patients may contribute to the assumption that their painful musculoskeletal (MSK) symptoms are weight related. 3 However, the published literature does not support the association between weight and many MSK conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that weight reduction improves functional health, for example, surgically induced weight loss is associated with a marked relief in dyspnea and chest pain. 25,26 However, symptoms like these could also be interpreted as reactions to underlying mental stress, predisposing a life-style causing obesity, and consequently amplify the condition specific problems.…”
Section: Discussionmentioning
confidence: 99%